2007
DOI: 10.1111/j.1540-8159.2007.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Venous Obstruction After Pacemaker Implantation

Abstract: This is the first systematic study to quantify venous changes after PM or ICD implantation. Our study shows that venous anomalies rendering PM implantation difficult are not infrequent. The incidence of new venous obstruction was 14%. Atrial fibrillation and biventricular PM implantation were independent predictors of venous obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 26 publications
3
99
0
15
Order By: Relevance
“…Digital subtraction venography, as utilized in most recent studies, has allowed a more precise evaluation of the venous territory, increasing the diagnostic precision, which was previously restricted to severe or total obstructions. With this methodology, the estimated incidence of lesions ranges from 14 to 64% of total implantations [1][2][3][4][5][6][7][8][9][10][11][12]. The incidence of venous lesions of 57.1%, observed in the Placebo Group of the current study, is in agreement with the results reported by most of these studies [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Rr = Relative Risk; Rar = Reduction Of Absolute Risksupporting
confidence: 82%
See 4 more Smart Citations
“…Digital subtraction venography, as utilized in most recent studies, has allowed a more precise evaluation of the venous territory, increasing the diagnostic precision, which was previously restricted to severe or total obstructions. With this methodology, the estimated incidence of lesions ranges from 14 to 64% of total implantations [1][2][3][4][5][6][7][8][9][10][11][12]. The incidence of venous lesions of 57.1%, observed in the Placebo Group of the current study, is in agreement with the results reported by most of these studies [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Rr = Relative Risk; Rar = Reduction Of Absolute Risksupporting
confidence: 82%
“…Recently, other risk factors have been described such as infection [7], lack of anticoagulation therapy [9,12], female hormones [9], previous history of thrombosis [9], multiple electrodes [9], atrial fibrillation [11], multisite pacemakers [11], previous implantation of a definitive pacemaker [8] and implantable cardioverter-defibrillator electrode lead with a double coil [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations